2018
DOI: 10.1101/483842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human online adaptation to changes in prior probability

Abstract: Optimal sensory decision-making requires the combination of uncertain sensory signals with prior expectations. The effect of prior probability is often described as a shift in the decision criterion. Can observers track sudden changes in probability? To answer this question, we used a change-point detection paradigm that is frequently used to examine behavior in changing environments. In a pair of orientation-categorization tasks, we investigated the effects of changing probabilities on decision-making. In bot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…The authors concluded that people can approximate an optimal Bayesian observer by using a switching heuristic that forgoes multiplying prior and sensory likelihood. In another study, Norton, Acerbi, Ma, and Landy (2018) compared subjects’ behavior to the “optimal” strategy, as well as several other heuristic models. The model fit showed that participants consistently computed the probability of a stimulus as belonging to one of two categories as a weighted average of the previous category types, giving more weight to those seen more recently; subjects’ responses also showed a bias toward seeing each prior category equally often (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that people can approximate an optimal Bayesian observer by using a switching heuristic that forgoes multiplying prior and sensory likelihood. In another study, Norton, Acerbi, Ma, and Landy (2018) compared subjects’ behavior to the “optimal” strategy, as well as several other heuristic models. The model fit showed that participants consistently computed the probability of a stimulus as belonging to one of two categories as a weighted average of the previous category types, giving more weight to those seen more recently; subjects’ responses also showed a bias toward seeing each prior category equally often (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In order to quantitatively evaluate the algorithm and following a similar strategy as [63], we computed an overall cost C as the negative log-likelihood (in bits) of the predicted probability bias, knowing the true probability and averaged over all T trials:…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…showing that learning about a hidden variable such as observers' priors can be accounted for by an exponential averaging model (Norton et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the fixed-effects analysis (see Table 2 for details), the Bayesian learner was substantially better than the instantaneous learner across all three experiments, but outperformed the exponential learner reliably only in the sinusoidal sequence. Likewise, the random-effects analysis based on hierarchical Bayesian model selection (Penny et al, 2010, Rigoux et al, 2014) showed a protected exceedance probability that was substantially greater for the Bayesian learner (Sin, RW2) or the exponential learner (RW1, RW2) than for the instantaneous learner ( Figure 4F). However, the direct comparison between the Bayesian and the exponential learner did not provide consistent results across experiments.…”
Section: Notementioning
confidence: 92%
See 1 more Smart Citation